IMPLEMENTATION OF PUBLIC SERVICE ON WORKING HEALTH SECTOR IN PAMEKASAN CALL CARE PROGRAM IN PAMEKASAN - Alimuddin, M Taufik (Airlangga Development Journal, 2024)
Public service is the fulfillment of the wishes and needs of the community by state administrators. The basis of the establishment of the state is to meet the welfare of the people. It is the duty of the state to meet the needs of the people. One of them is the need for good health and easy access. To meet the community's need for access to health care, the Regent of Pamekasan, Baddrut Tamam, initiated a program called Pamekasan Call Care where the program is a priority program in Pamekasan. This program provides many cars spread over 178 villages located in 13 sub-districts in Pamekasan district. People who need assistance in accessing health simply call the available phone number and they will immediately be picked up to be delivered to the desired health facility. Although it has been implemented since 2020, it turns out that the implementation of this program has not been without obstacles. Problems such as the lack of the number and competence of existing human resources and limited accessibility make this a challenge for the Pamekasan Call Care program.